Some biochemical components and biological activity of the placenta-free fruit juice of Momordica charantia L. - Ha, Hoang Thu; Tran Chau, Pham Thi (Academia Journal of Biology, 2006)
This work dealt with analysis of placenta-free fruits (PFF) of M. charantia. After removing the placenta of 50 kg of M. charantia fresh fruits, 42,65 kg of PFF were obtained. This PFF contained 7% of dry substances, of which 0.18% were proteins. The clarified juice (17.25 l) obtained from PFF of M. charantia was subjected to study. The proteolytic activity (PA) of this juice was rather low and almost the same in the range of pH from 5.5 to 7.6. By fractionating this juice on sephadex G-50 column, only one protein peak was obtained. By using SDS-PAGE method, 9 protein bands were detected and Mr of 4 major bands were found to be in the range of 35 kD to 50 kD. The placenta-free fruit juice of M. charantia inhibited the growth of 4 strains of Staphylococcus aureus isolated from patient wound pus. Basing on the obtained results, it was suggested that proteins of PFF contributed to their antibacterial activity.